Challenging Colonialism through Tarekat Syattariyah and Pesantren: The Conceptual Thought of Kiai Hasan Maolani, 1836–1842 - Darmawan Rahmadi; Agus Kusman; Khairunisa Ashriana; Novia Poni Agustiyani (Mahesa Research Center (PT. Mahesa Global Publishing), 2025)
This study explores the educational contributions and intellectual legacy of Kiai Hasan Maolani, a prominent Islamic scholar who lived during the Dutch colonial era in Kuningan Regency, West Java. The research centers on his biography and his significant role as both a religious and educational figure, whose influence extended beyond regional boundaries, attracting students from Central and East Java. Employing a historical method that integrates heuristics, source criticism, interpretation, and historiography, this study utilizes both primary and secondary sources to reconstruct his educational activities. The findings reveal that Kiai Hasan Maolani founded Pesantren Lengkong, which emerged as a vital institution for Islamic religious education and intellectual development. Through this pesantren, he implemented a holistic educational philosophy encompassing key concepts such as the pursuit of knowledge (thalabul 'ilm), worship (ibadah), Islamic monotheism (tawhid), social cohesion through visits and religious networking (silaturahmi and ziyarah), charitable practices (amal), and spiritual struggle (jihad). The research concludes that Kiai Hasan Maolani’s educational model not only shaped the intellectual character of his time but also laid the foundation for a resilient pesantren-based learning tradition in West Java.